Visualisasi Sebaran Wilayah Usaha Izin Pertambangan Aktif Mineral Bukan Logam di Provinsi Sumatera Barat Berbasis WebGIS - Fadila, Rahayu; Yulfa, Arie (YASIN, 2024)
West Sumatra Province is an area that has vast and very rich mining potential. However, focusing on the field, of course there are still many mining obstacles that need to be fixed. An example of the problem is, the ESDM Service has a central information system in the form of spatial data and others, the existing system was previously built for the company as a self-service. The regional ESDM does not have access to manage and register licensed companies to the Center system. This study aims to implement visualization of the distribution of active non-metallic mineral mining permit business areas in West Sumatra Province based on WebGIS. This type of research uses the Research and Development method. This method is used to produce certain products after analyzing the needs and testing the effectiveness of the product to see if the product works. The data used for visualization is the Mining Business Permit Area (WIUP) data for West Sumatra Province. The data analysis technique uses the waterfall technique and functionality testing of the product. The results of this study are to produce a digital product in the form of WebGIS distribution of active non-metallic mineral mining permit business areas in West Sumatra Province. The conclusion in this study is the implementation of WebGIS for the distribution of active mining permit business areas in West Sumatra Province and has proven to work well as evidenced by the functionality accuracy test.